Mandat Ilahi tentang Menggembalakan Domba - Indriati Tjipto Purnomo (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
AbstractShepherd is one of the four kinds of offices that are given responsibility by God and placed in thechurch and function for building the body of Christ. The shepherd is the leader who brings thecongregation to maturity in Christ, Ephesians 4:11. God calls and places someone to be a shepherdto carry out the Divine mandate, which is to shepherd the sheep. The linguists in this study use aqualitative method, namely a theological review presented using literature or literature studies